تحسين اكتشاف المعرفة باستخدام تطبيقات التنقيب عن البيانات - حنا جبر; الكردي فاتن (Latakia University Journal -Engineering Sciences Series, 2018)
تم من خلال هذه الدراسة استخدام التنقيب عن البيانات Data Mining على موقع ويب مختص بتجارة القطع الالكترونية ومعدات الحواسيب من خلال بعض الخدمات مثل خدمة المنتجات التي تم شراؤها معا Frequently Bought Together تعتمد هذه الخدمة على خوارزمية الترابطAssociation، وتم استخدام هذه الخدمة على صفحة طلب منتج، أي عندما يقوم زبون بطلب منتج معين تظهر له قائمة بالمنتجات الأكثر مبيعاً مع المنتج المطلوب. الخدمة الثانية هي خدمة تفضيلات المستخدمين Get Personalized Recommendationsوتعتمد هذه الخدمة على خوارزمية العنقدةClustering، حيث تظهر مجموعة المنتجات المتوقع أن يطلبها الزبون وذلك حسب بيانات الزبون، تظهر هذه الخدمة على صفحة الزبون. وخدمة عرض تنبؤ مبيعات الموقع تعتمد هذه الخدمة على خوارزمية التسلسل الزمنيTime Series، حيث تُظهر هذه الخدمة لمدير النظام توقع أرباح الموقع لفترة مستقبلية قادمة. We Use technologies and methodologies of building the web applications to design and build an E-commerce Website. This website is specialist in trading with electronic parts and computer equipment. Then implement Data Mining techniques on this website by adding the following services:Frequently Bought Together Service: This service depends on Association algorithms, it shows the service on request product page, when a customer requests for a particular product. It shows him the list of best-selling products with the desired product. Next, there is Get Personalized Recommendations Service: This service depends on Clustering algorithms, where the expected range of products shows that the customer requested, according to the specifications, this service appear on the customer page. In addition,Will Be Service: This service relies on Time Series algorithms, where this service showing to the system administrator predicted earnings of website for a future period.